Salivary IgA Depression in Drug-Influenced Gingival Enlargement among Hypertensive Patients - Sabarudin, Muhammad Annurdin; Taib, Haslina; Wan Mohamad, Wan Majdiah; Zainuddin, Siti Lailatul Akmar; Wan Ghazali, Wan Syamimee; Misran, Ahmad Azhar (Journal of Dentistry Indonesia, 2022)
Drug-influenced gingival enlargement (DIGE) among hypertensive patients is commonly associated with antihypertensive drugs such as calcium channel blockers (CCBs). Immune response alteration is one of the proposed mechanisms for DIGE. Immunoglobulin A (IgA) in saliva which involves in defense mechanism was shown to be affected in patients with DIGE. Objective: This study aimed to determine the association of salivary IgA level with DIGE. Methods: This cross-sectional study comprised 47 hypertensive patients who had consumed antihypertensive drugs for at least 3 months. Twenty-one (44.7%) males and 26 (55.3%) females had participated in this study. Data was analyzed using SPSS version 26.0. The p-value of less than 0.05 at a 95% confidence interval is considered statistically significant. Results: Eighty-three percent and 17.0% of hypertensive patients were on CCBs and non- CCBs respectively. Amlodipine was found to be the most common (55.3%) antihypertensive drug consumed. Twenty- one (44.7%) patients presented with DIGE. The salivary IgA level was significantly decreased (p=0.03) among hypertensive patients with DIGE [Median 4.9 ng/mL (IQR 5.268)] compared to those without DIGE [median 15.03 ng/mL (IQR 32.246)]. Conclusion: This data indicates the level of salivary IgA was significantly affected in patients with DIGE which may compromise the defense mechanism of saliva.